2007
DOI: 10.1038/sj.mp.4002011
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in GABA-related transcriptome in the dorsolateral prefrontal cortex of subjects with schizophrenia

Abstract: In subjects with schizophrenia, impairments in working memory are associated with dysfunction of the dorsolateral prefrontal cortex (DLPFC). This dysfunction appears to be due, at least in part, to abnormalities in c-aminobutyric acid (GABA)-mediated inhibitory circuitry. To test the hypothesis that altered GABA-mediated circuitry in the DLPFC of subjects with schizophrenia reflects expression changes of genes that encode selective presynaptic and postsynaptic components of GABA neurotransmission, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
453
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 462 publications
(495 citation statements)
references
References 72 publications
(135 reference statements)
33
453
4
1
Order By: Relevance
“…4,[75][76][77][78][84][85][86][87][88] Importantly, just as in our current study of BDNF- ablated animals, SST, NPY and RGS4 transcripts are downregulated in the prefrontal cortex (PFC) of subjects with schizophrenia. 29,89,90 However, we acknowledge that other, BDNF-independent mechanisms may also account for the altered expression of these genes in schizophrenia. 91,92 The extent to which a BDNF-dependent transcriptome profile is present in schizophrenia remains to be established in hypothesis-driven assessment of gene expression changes in the human PFC.…”
Section: Discussionmentioning
confidence: 95%
“…4,[75][76][77][78][84][85][86][87][88] Importantly, just as in our current study of BDNF- ablated animals, SST, NPY and RGS4 transcripts are downregulated in the prefrontal cortex (PFC) of subjects with schizophrenia. 29,89,90 However, we acknowledge that other, BDNF-independent mechanisms may also account for the altered expression of these genes in schizophrenia. 91,92 The extent to which a BDNF-dependent transcriptome profile is present in schizophrenia remains to be established in hypothesis-driven assessment of gene expression changes in the human PFC.…”
Section: Discussionmentioning
confidence: 95%
“…Although robust changes in cortical GAD67 mRNA are not typically found in the PFC of individuals with depression (Thompson et al, 2009;Sibille et al, 2011), significant decreases in somatostatin suggest that interneuron deficits may be especially prominent in a subset of interneurons shown to directly contribute to cortical plasticity (Lazarus and Huang, 2011). As inhibitory interneuron deficits are shared among those with depression, bipolar disorder, and schizophrenia (Thompson et al, 2009(Thompson et al, , 2011Fung et al, 2010;Hashimoto et al, 2008;Daskalakis et al, 2002), cortical plasticity deficits would also be expected to be found in multiple forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The GABAergic connection between PFC and other brain structures is probably also involved in modulation of anxiety-related behaviours (28,29). Previous studies have reported that GABA-containing neurons in the rat ventral tegmental area project to the PFC and GABAergic projections from PFC also innervate different brain regions such as the nucleus accumbens (11,30).…”
Section: Discussionmentioning
confidence: 99%